2016
DOI: 10.1111/jfpp.12778
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Thin-Layer Drying of Turnip Slices Under Semi-Industrial Continuous Band Dryer

Abstract: This study aims at investigating the thin‐layer drying behavior of turnip slices in a multistage semi‐industrial continuous band dryer. Turnip slices with the thickness of 4 mm were used for the drying experiments. The experiments were conducted at three air temperatures of 45, 60, and 75C, three air velocities of 1, 1.5, and 2 m/s, and three belt linear speeds of 2.5, 6.5, and 10.5 mm/s with three replications for each treatment. To estimate the drying kinetic of turnip slices, six mathematical models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…D eff for agricultural and food products can vary between 10 −12 and 10 −8 m 2 /s (Kaveh & Amiri Chayjan, ). The D eff values for this study are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…D eff for agricultural and food products can vary between 10 −12 and 10 −8 m 2 /s (Kaveh & Amiri Chayjan, ). The D eff values for this study are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The total drying time was considerably decreased with rising air temperature. This decreasing can be because of the point that higher air temperature causes larger vapor pressure difference among surface and center of tarragon (Kaveh & Amiri Chayjan, ). Similar results were observed by Onwude, Hashim, Janius, Nawi, and Abdan () for drying of Pumpkin Slices, Santacatalina, Soriano, Cárcel, and Garcia‐Perez () for drying of eggplant and Junqueira, Correa, and Ernesto () for drying of cape gooseberry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Figure presents the amount of ( D eff ) of tarragon at different conditions achieved by Equation . Based on the literature, the amount of D eff is ranged within 10 −12 to 10 −8 m 2 /s for agriculture product using the drying methods (Kaveh & Amiri Chayjan, ). According to the results, the values of D eff for tarragon varied between 1.34 × 10 −10 to 2.74 × 10 −10 m 2 /s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANN can establish a functional relationship between input and output variables by training and learning (Chojaczyk, Teixeira, Neves, Cardoso, & Guedes Soares, ). In recent years, ANN models have been studied for the modeling of drying of potato cubes (Azadbakht, Aghili, Ziaratban, & Torshizi, ), bay leaves (Aktaş, Şevik, Özdemir, & Gönen, ), mango ginger (Murthy & Manohar, ), sour cherry (Motavali, Najafi, Abbasi, Minaei, & Ghaderi, ), onion (Jafari, Ganje, Dehnad, & Ghanbari, ), kiwi (Mahjoorian et al, ), zucchini (Tavakolipour, Mokhtarian, & Kalbasi‐Ashtari, ), green bell pepper (Jafari, Ghanbari, Ganje, & Dehnad, ), and turnip slices (Kaveh & Chayjan, ). But, there is no study about comparison between ANN model and mathematical models for PVOD treated and non‐pretreated figs during drying.…”
Section: Introductionmentioning
confidence: 99%